IMAGINATIVE POSSIBILITIES OF HARRY GORDON`S POETRY - Еlena I. Seifert (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The author of the article examines the lyrics of the poet and artist Harry Gordon through the category of intermediality, discovering the unique visual possibilities of his word when creating ekphrasises in the narrow sense of the word (“translations from the language of painting”) and works in the author`s artistic form – “daguerreotypes”. The use of the word as a pictorial tool to create artistic imagery by poet Harry Gordon is of scholarly interest. The study is based on the theory of intermediality. The category of “intermediality”, primarily known from the works of the German scholar Aage A. Hansen-Löwe, has been further developed by a number of scholars. Gordon’s landscapes appear as (framed) paintings; portraits are masterfully created; contour, colour, outline actively work along with the word. Literature does not belong to the expressive, but to the fine arts, which can display the contours of actual reality, but the share of representationalism in the poems and the optics of the artists of the word are undoubtedly different. Harry Gordon is a poet in poetry, a painter in painting. However, the intermediality and ekphrastic nature of his poetry is extremely interesting: the poet combines words, colours and outlines as a means of creating artistic imagery, he creates poems as “translations from the language of painting”, literary ekphrasis, works with a multiview lens. The art form, which Harry Gordon called the “daguerreotypes”, is often titled with visual motifs. Often these are images from the lyrical protagonist`s childhood, but a number of them belong to the present. They are mediators that take the protagonist back to the world of childhood, such as the alarm clock. Odessa and, more broadly, maritime motifs (“Dophinovka”, “Privoz”, “Bread Harbour”, “Liman”) are autobiographical. Gordon’s daguerreotypes are mostly images from his childhood, imprinted on the retina of the lyrical character. The lyrical protagonist is often an observer (sometimes the title even specifies the angle from which the observation is made: “At the window”), but often he is also the subject, sometimes observed by another lyrical character, or even an object mentioned but not in the picture. Often Gordon’s poetic pictures are filled with the gamut of experiences of the lyrical self, such as childhood fears, shame and embarrassment, lingering curiosity, excitement, a sense of freshness, longing, etc. With a clear predominance of visual motifs (and even endowing non-visible phenomena with the properties of the visual), Gordon’s “daguerreotype” depicts a picture with sound, smell, taste and tactile sensations. As a result of the study, it has been found that Gordon’s depiction is acquired by sound, olfactory, tactile, gustatory images, with the predominance of the visual, an exchange of signs is observed between the images generated by different senses